The last-stadium larva and systematic status of Planaeschna suichangensis Zhou &Wei, 1980 (Odonata: Anisoptera: Aeshnidae) - Xu, Qi-Han; Zhang, Hao-Miao (Zootaxa, 2011)
The final stadium larva of Planaeschna suichangensis is described and illustrated. Its larval morphological characters indicate that P. suichangensis is a valid species closer to P. risi than to P. taiwana.